Understanding inclusion : core concepts, policy and practice - Woolley, Richard (New York : Routledge, 2018)
'Understanding Inclusion is a rich, comprehensive exploration of inclusion in education, challenging us to think about being'inclusive' in its broadest sense. It unpicks a wide range of complex themes and issues that impact on educational practice, supporting educational professionals in helping teachers and learners understand difference as the norm, and not the exception.'--Back cover.
Introducing Inclusion -- Social Inclusion and Social Class -- Education and Global Dimensions -- Learners and Learning -- Multilingualism : Overcoming Policy Constraints -- Religion and Belief -- Dis/ability -- Gender Diversity -- Aspirations and Social Mobility -- Sexual Behaviours and Development -- Teaching Assistants and Inclusion - Inclusion and the Arts - Restorative Justice - Leadership and Inclusion.
Includes bibliographical references and index.
Keywords: Inclusive education